Best practice when working with suicidal behaviour and self-harm in primary care: a qualitative exploration of young people's perspectives. Issue 10 (28th October 2020) - Bellairs-Walsh, India; Perry, Yael; Krysinska, Karolina; Byrne, Sadhbh J.; Boland, Alexandra; Michail, Maria; Lamblin, Michelle; Gibson, Kerry L.; Lin, Ashleigh; Li, Tina Yutong; Hetrick, Sarah; Robinson, Jo
Abstract : Objectives: General practitioners (GPs) have a key role in supporting young people who present with suicidal behaviour/self-harm. However, little is known about young people's opinions and experiences related to GPs' practices for such presentations, and their decisions to disclose suicidal behaviour/self-harm to GPs. Additionally, existing guidelines for the management of suicide risk and/or self-harm have not incorporated young people's perspectives. This study aimed to explore young people's views and experiences related to the identification, assessment and care of suicidal behaviour and self-harm in primary care settings with GPs. Design, setting and participants: Two qualitative focus groups were conducted in Perth, Western Australia, with 10 young people in total ( M age = 20.67 years; range: 16–24). Data were collected using a semistructured, open-ended interview schedule and analysed using thematic analysis. Results: Five major themes were identified from the focus groups. (1) Young people wanted a collaborative dialogue with GPs, which included being asked about suicidal behaviour/self-harm, informed of treatment processes and having autonomy in decision making; (2) young people were concerned with a loss of privacy when disclosing suicidal behaviour/self-harm; (3) young people viewed labels and assessments as problematic and reductionist—disliking the terms 'risk' and 'risk assessment', and assessment approaches that are binary and non-holistic; (4) young people highlighted the importance of GPs' attitudes, with a genuine connection, attentiveness and a non-judgemental demeanour seen as paramount; and (5) young people wanted to be provided with practical support and resources, followed-up, and for GPs to be competent when working with suicidal behaviour/self-harm presentations. Conclusions: Our study identified several concerns and recommendations young people have regarding the identification, assessment and care of suicidal behaviour/self-harm in primary care settings. Taken together, these findings may inform the development of resources for GPs, and support progress in youth-oriented best practice.